Until It's a regulation It's not my fight: Complexities of a voluntary nonlead hunting ammunition program. (1st January 2021) - Schulz, John H.; Wilhelm Stanis, Sonja A.; Hall, Damon M.; Webb, Elisabeth B.
Abstract: Wildlife and human health are at risk of lead exposure from spent hunting ammunition. Lead exposure persists for bald eagles due to bullet fragments in game animal gut piles and unretrieved carcasses, and is also a human health risk when wild game is procured using lead ammunition. Programs encouraging the voluntary use of nonlead ammunition have become a popular approach mitigating these effects. This study explored attitudes and experiences of United States Fish and Wildlife Service (USFWS) staff implementing an outreach program encouraging deer hunters to voluntary use nonlead ammunition on 54 National Wildlife Refuges (NWRs) in the Upper Midwest, U.S. to understand factors affecting program implementation. We conducted 29 semi-structured interviews of USFWS staff along with 60 responses from an open-ended survey question. Twelve themes emerged from the data and were grouped into three broad categories: (1) challenges of dealing with complex issues, (2) importance of messengers and messages, and (3) resistance from staff. Challenges of dealing with complex issues included administrative restraint and uncertainty, scope and scale of program, human health not an agency responsibility, contextual political influences, and public-private collaborations. Importance of messengers and messages included the importance of experience, and salience of human health risk. Finally, resistance from staff included skepticism of the science and motives behind the program, competing priorities for refuge staff, differing perceptions of regulatory and voluntary approaches, cost and availability of nonlead ammunition, and disregard by some about lead ammunition and human health risks. Staff identified numerous challenges implementing the program, many of which were external factors beyond the control of the participants. Understanding the factors affecting program implementation may help guide future efforts encouraging the voluntary use of nonlead ammunition. Highlights: Perceptions of refuge staff were examined about a voluntary nonlead ammunition program. Multiple socio-political issues helped to identify challenges implementing the program. Key factors; nonlead cost/availability, credibility, human health, and partnerships. Voluntary nonlead programs have limited ability to reduce lead ammunition use.